Profile Patients based on Risk Factors for Ischemic Stroke in the Neurology Inpatient Ward of Dr. Soetomo General Academic Hospital Surabaya during the Period of January to June 2022 - Kusuma, Nabila Divandra; Ardhi, Mohammad Saiful; Widodo, Widodo; Setyowatie, Sita (Universitas Airlangga, 2024)
Highlight: Some risk factors exhibited incongruent outcomes and went against existing theories. The age group under 65 years old was the most prevalent modifiable risk factor. Stage 2 hypertension was the most dominant non-modifiable risk factor. ABSTRACT Introduction: Stroke is a major cause of disability and death worldwide. Among the three types of strokes, the ischemic stroke is the most prevalent. Controlling risk factors is a key approach to preventing ischemic stroke. Due to the limited data availability in Indonesia, it is important to research patient profiles focusing on risk factors for ischemic stroke. Objective: To record the patient profiles based on the risk factors for ischemic stroke in the neurology inpatient ward of Dr. Soetomo General Academic Hospital Surabaya for the period of January–June 2022. Methods: This was a descriptive observational study with a retrospective design. This study examined secondary data from ischemic stroke patients’ medical records at the Dr. Soetomo General Academic Hospital’s neurology inpatient ward in Surabaya between January and June 2022. Results: Out of 176 patients, 108 were under the age of 65. Of these, 97 were male. There were 63 patients with a history of ischemic stroke, 58 with diabetes mellitus, 84 with stage 2 hypertension, 77 with dyslipidemia, 59 with impaired kidney function, 52 with diabetes mellitus by lab tests, and 23 who smoked. Conclusion: In this study, some risk factors exhibited discrepancies and contradicted existing theories. The two dominant variables in the patient population were a combination of risk factors that occur more frequently at a certain age and a combination of risk factors in patients with recurrent strokes.